The role of oxidative stress in intervertebral disc cellular senescence - Cheng, Fengqi; Yang, Honghao; Cheng, Yunzhong; Liu, Yuzeng; Hai, Yong; Zhang, Yangpu (Frontiers in Endocrinology, 2022)
With the aggravation of social aging and the increase in work intensity, the prevalence of spinal degenerative diseases caused by intervertebral disc degeneration（IDD）has increased yearly, which has driven a heavy economic burden on patients and society. It is well known that IDD is associated with cell damage and degradation of the extracellular matrix. In recent years, it has been found that IDD is induced by various mechanisms (e.g., genetic, mechanical, and exposure). Increasing evidence shows that oxidative stress is a vital activation mechanism of IDD. Reactive oxygen species (ROS) and reactive nitrogen species (RNS) could regulate matrix metabolism, proinflammatory phenotype, apoptosis, autophagy, and aging of intervertebral disc cells. However, up to now, our understanding of a series of pathophysiological mechanisms of oxidative stress involved in the occurrence, development, and treatment of IDD is still limited. In this review, we discussed the oxidative stress through its mechanisms in accelerating IDD and some antioxidant treatment measures for IDD.